Primer design, in silico PCR and optimum annealing temperature for Escherichia coli detection in refillable drinking water samples - Afifatul Achyar; Annisa Irna Putri; Dwi Hilda Putri; Yuni Ahda (Tropical Genetics, 2021)
Refill Drinking Water Depots (DAMIU) in the community are easy to find at affordable prices, which is a concern in the feasibility of refill drinking water quality. E.coli is one of the pathogenic bacteria present in drinking water that has poor quality. When it enters the body it can cause symptoms of diarrhea, fever, vomiting and others. The purpose of this study was to create a specific primer for E.coli that can be used to detect E.coli and determine the optimum temperature of primer annealing. Researchers do a new primer design because the existing design does not necessarily produce the same results due to various factors of different experimental conditions. The primer design was carried out on an in silico-based and had to meet the criteria for a good primer because it would be used in vitro. E.coli gene sequences was aligned with Shigella sp. using Pairwise Alignment. Primer candidates were analyzed using NCBI's Primer3 and Geneious Prime tools. The result is that the first primer pair is forward 5'–ATGCAGTGGTTCCTTATCTCACA-3' reverse 5'- ATCCTTAATGGCACTGCGCT-3', amplifying the amplicons along 417 bp in the yraJ gene. The second primer pair, forward 5'-CAGAACGTTTTTCATTCAGCAGG-3' reverse 5'-GCCACTACCAGATCGAGTCA-3' amplifies the 573 bp amplicon in the rne gene. The optimum annealing temperature for both pairs of primers was 59.5oC.